2014
DOI: 10.1021/jf5033075
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trace Microcystins in Vegetables Using Solid-Phase Extraction Followed by High Performance Liquid Chromatography Triple-Quadrupole Mass Spectrometry

Abstract: A selective and sensitive method for the simultaneous detection of three common and hazardous microcystins (microcystins-LR, -RR, and -YR) in various vegetables was established using solid-phase extraction followed by high performance liquid chromatography coupled with mass spectrometry. The methanol-water proportion ratio of the extraction solvent and its acidity, as well as the efficiencies of solid-phase extraction, were evaluated to optimize a pretreatment procedure for extracting the microcystins from 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 40 publications
5
67
5
Order By: Relevance
“…[13,14] . Today, MCs are of particular health concern as they are contaminants of sea foods, vegetables, and drinking water industries [15] , thus, the World Health Organization (WHO) recommends a Page 3 of 17 A c c e p t e d M a n u s c r i p 3 threshold limit of 1.0 µg·L -1 MC-LR in drinking water [16] . Therefore, a rapid, sensitive, and accurate analytical method is of particular importance for the determination of MCs in environmental water samples.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] . Today, MCs are of particular health concern as they are contaminants of sea foods, vegetables, and drinking water industries [15] , thus, the World Health Organization (WHO) recommends a Page 3 of 17 A c c e p t e d M a n u s c r i p 3 threshold limit of 1.0 µg·L -1 MC-LR in drinking water [16] . Therefore, a rapid, sensitive, and accurate analytical method is of particular importance for the determination of MCs in environmental water samples.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Järvenpää et al [138] reported that microcystins were detected on roots (a non-edible plant tissue for human but can be for animal) but not detected in leaves of mustard and broccoli. Furthermore, numerous studies concerning accumulation of cyanotoxins in agronomic plants growing in the soil were reported in radish roots, leaves of arugula and dill [61], in rice grains [65], in leaves of lettuce and cabbage [61,139], in leaves and stems of water spinach [139] and in fruits and seeds of tomato and pepper [64]. However, a recent study based on the use of 14 C-labelled MC-LR showed that tomato fruits did not accumulate the toxin [92].…”
Section: Bioaccumulation Of Cyanotoxins In Agricultural Plants and Comentioning
confidence: 99%
“…Among these cyanotoxins, microcystins (MCs) and cylindrospermopsin (CYN) are amongst the most studied because of their widespread distribution. MCs, mainly produced by Microcystis , have the common cyclic heptapeptidic structure of cyclo(- d -Ala- l -X- d -MeAsp- l -Z-Adda- d -Glu-Mdha), in which X and Z are variable l -amino acids that give the name to the molecule [ 4 ]. Because of these modifications, and the methylation/desmethylation of several functional groups, more than 100 MC variants have been reported to date [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CYN is an alkaloid consisting of a tricyclic guanidine moiety combined with hidroxymethiluracil, which can be produced by Cylindrospermopsis raciborskii and Chrysosporum ovalisporum [ 7 ]. Concerning the mechanism of action, MCs are hepatotoxins and tumor promoters due to their strong potent inhibition of protein phosphatases and the effect on cell signaling pathways [ 4 ]. CYN is well known by its inhibition of protein and glutathione synthesis, induction of oxidative stress, and cytochrome P450 seems to mediate its toxicity; its pro-genotoxic activity has also been studied [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%